THE ROLE OF PEDAGOGY IN THE LIFE OF SOCIETY AND MAN - Setsaliyeva Ilmira Ismailovna (Galaxy International Interdisciplinary Research Journal, 2022)
Intelligent presentation of subject pedagogy, object pedagogy, system pedagogy. Rol pedagogiki v obshchestve i jizni cheloveka, rol v professionsii uchitelya, razvitie samostoyatelnogo myshleniya, tvorcheskix knobostey i professionalnyx interesov uchashchixsya.